If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X(6x + -3) = (6x + 9)(x + -8) Reorder the terms: X(-3 + 6x) = (6x + 9)(x + -8) (-3 * X + 6x * X) = (6x + 9)(x + -8) (-3X + 6xX) = (6x + 9)(x + -8) Reorder the terms: -3X + 6xX = (9 + 6x)(x + -8) Reorder the terms: -3X + 6xX = (9 + 6x)(-8 + x) Multiply (9 + 6x) * (-8 + x) -3X + 6xX = (9(-8 + x) + 6x * (-8 + x)) -3X + 6xX = ((-8 * 9 + x * 9) + 6x * (-8 + x)) -3X + 6xX = ((-72 + 9x) + 6x * (-8 + x)) -3X + 6xX = (-72 + 9x + (-8 * 6x + x * 6x)) -3X + 6xX = (-72 + 9x + (-48x + 6x2)) Combine like terms: 9x + -48x = -39x -3X + 6xX = (-72 + -39x + 6x2) Solving -3X + 6xX = -72 + -39x + 6x2 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Reorder the terms: 72 + -3X + 39x + 6xX + -6x2 = -72 + -39x + 6x2 + 72 + 39x + -6x2 Reorder the terms: 72 + -3X + 39x + 6xX + -6x2 = -72 + 72 + -39x + 39x + 6x2 + -6x2 Combine like terms: -72 + 72 = 0 72 + -3X + 39x + 6xX + -6x2 = 0 + -39x + 39x + 6x2 + -6x2 72 + -3X + 39x + 6xX + -6x2 = -39x + 39x + 6x2 + -6x2 Combine like terms: -39x + 39x = 0 72 + -3X + 39x + 6xX + -6x2 = 0 + 6x2 + -6x2 72 + -3X + 39x + 6xX + -6x2 = 6x2 + -6x2 Combine like terms: 6x2 + -6x2 = 0 72 + -3X + 39x + 6xX + -6x2 = 0 Factor out the Greatest Common Factor (GCF), '3'. 3(24 + -1X + 13x + 2xX + -2x2) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(24 + -1X + 13x + 2xX + -2x2)' equal to zero and attempt to solve: Simplifying 24 + -1X + 13x + 2xX + -2x2 = 0 Solving 24 + -1X + 13x + 2xX + -2x2 = 0 Move all terms containing X to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -1X + 13x + 2xX + -24 + -2x2 = 0 + -24 Reorder the terms: 24 + -24 + -1X + 13x + 2xX + -2x2 = 0 + -24 Combine like terms: 24 + -24 = 0 0 + -1X + 13x + 2xX + -2x2 = 0 + -24 -1X + 13x + 2xX + -2x2 = 0 + -24 Combine like terms: 0 + -24 = -24 -1X + 13x + 2xX + -2x2 = -24 Add '-13x' to each side of the equation. -1X + 13x + 2xX + -13x + -2x2 = -24 + -13x Reorder the terms: -1X + 13x + -13x + 2xX + -2x2 = -24 + -13x Combine like terms: 13x + -13x = 0 -1X + 0 + 2xX + -2x2 = -24 + -13x -1X + 2xX + -2x2 = -24 + -13x Add '2x2' to each side of the equation. -1X + 2xX + -2x2 + 2x2 = -24 + -13x + 2x2 Combine like terms: -2x2 + 2x2 = 0 -1X + 2xX + 0 = -24 + -13x + 2x2 -1X + 2xX = -24 + -13x + 2x2 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| -4(5y-7)-y=-2(y-5) | | x*y=630 | | x(2x+3)=4 | | 3(x-8)=9x | | 3x+9-2x=13 | | 4x^4-20x^2+16=0 | | 26x+12=5(5x+4) | | 10-(2*-4)+3x=16 | | (5u+3)(5-u)=0 | | 3x+9-2x=14 | | 2x-6x+9=x-6+15 | | (7x^2+5x)/(x^2+1)-5x/(x^2-6) | | 5w+2.7=12 | | 9x^2+169=0 | | 3x+9x-4=3(4x+9) | | -8=-(-6x-3) | | .5x-4=0 | | 2y+2(y-6)=8y-6(y-10) | | 9(x-1)=-126 | | 7/36*x=5 | | 4(x-2)=2x-2 | | 52=p-41 | | -(8x-4)-(3x-5)+10=-9(x-1)-(5x+8+3) | | 7x-2+5=10x+4 | | p+13=-10 | | 6x+9-5x=16 | | -2(3x-6)+5=-1 | | 8y=5y+9 | | Rx+Sy=Tfory | | (-5+7i)+(-8-9i)=0 | | (x)=3x+4 | | x-9/5-1=x-3/4 |